(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Online business has become a popular way of shopping for consumers. This innovation for shopping not only brings a great number and variety of merchandise to potential consumers but also offers numerous business activities and a huge market. Social media is no longer known as a platform that facilitates its users to present themselves on the internet but also as media to sell some products to consumers, known as online shops or selling. Researchers aim for customer satisfaction as before the pandemic, some things have also improved, like the means of purchasing food products. There are multiple ways to start an online food business in the Philippines. Because of technology enhancement, people can now easily shop, buy, and even post our product to sell, easily and more conveniently than before. This study utilized the descriptive method design for determining and gathering information about the customer satisfaction of small-scale online food businesses by BSHM students of Bestlink College of the Philippines. The researcher gathered data using simple random sampling techniques on their survey questionnaires and online interviews administered by Google Forms and online video calls to fifty (50) target respondents at Bestlink College of the Philippines. According to our researcher, they are more willing to undergo online shopping instead of buying in physical stores, less hustle, and more convenient. The speed of the delivery is more important to our consumer to perceive their satisfaction with the product. Some respondents agreed that spending too much in purchasing food is the easiest way to order food; customer satisfaction is an important income in this business to level up customer loyalty. And lastly, the consumer is comfortable with the cash-on-delivery payment method. Based on the gathered data, the online business has the edge here, as the selection is virtually endless, whereas stores can have more stock and are easy to purchase with the customer. In this research, you will learn about customer satisfaction in small online food businesses, especially when a pandemic is happening, and many businesses have been affected.